THE INFLUENCE OF MISSIONARY WORK ON SOCIO-POLITICAL RELATIONS IN THE CONTEXT OF GLOBALIZATION (Scientific journal of the Fergana State University, 2024)
This artisle analyzes the impast of missionary work on sosio-politisal relations in the sontext of globalization. The artisle also provides views on sestarianism, whish manifests itself on a global ssale, undermines interfaith harmony and awakens religious enmity.